Importance of accessibility and opening hours to overall patient experience of general practice: analysis of repeated cross-sectional data from a national patient survey - Cowling, Thomas E (Br J Gen Pract, 2018)
BACKGROUND: The UK government aims to improve the accessibility of general practices in England, particularly by extending opening hours in the evenings and at weekends. It is unclear how important these factors are to patients’ overall experiences of general practice. AIM: To examine associations between overall experience of general practice and patient experience of making appointments and satisfaction with opening hours. DESIGN AND SETTING: Analysis of repeated cross-sectional data from the General Practice Patient Surveys conducted from 2011–2012 until 2013–2014. These covered 8289 general practice surgeries in England. METHOD: Data from a national survey conducted three times over consecutive years were analysed. The outcome measure was overall experience, rated on a five-level interval scale. Associations were estimated as standardised regression coefficients, adjusted for responder characteristics and clustering within practices using multilevel linear regression. RESULTS: In total, there were 2 912 535 responders from all practices in England (n = 8289). Experience of making appointments (β 0.24, 95% confidence interval [CI] = 0.24 to 0.25) and satisfaction with opening hours (β 0.15, 95% CI = 0.15 to 0.16) were modestly associated with overall experience. Overall experience was most strongly associated with GP interpersonal quality of care (β 0.34, 95% CI = 0.34 to 0.35) and receptionist helpfulness was positively associated with overall experience (β 0.16, 95% CI = 0.16 to 0.17). Other patient experience measures had minimal associations (β≤0.06). Models explained ≥90% of variation in overall experience between practices. CONCLUSION: Patient experience of making appointments and satisfaction with opening hours were only modestly associated with overall experience. Policymakers in England should not assume that recent policies to improve access will result in large improvements in patients’ overall experience of general practice.